(untitled) (CIPEEX, 2025)
Leprosy is a chronic and infectious-contagious disease identified in the 19th century by Gehard Hansen. In Anápolis, Goiás, the prevalence of the disease has been high, with the city showing rates above the national average between 2007 and 2010. This work aims to correlate the incidence rates of Leprosy provided by the Municipal Health Department of Anápolis with the neighborhoods of Anápolis to produce geo-referencing. The study indicated that Anápolis has several neighborhoods with continuous cases of Leprosy. The research analyzed data from 2019 to 2024, revealing that the disease still affects multiple neighborhoods, including the Bairro de Lourdes and Jundiaí, although detailed geo-referencing was not possible. The study underscores the need for greater awareness and improvement of health policies to address Leprosy in Anápolis.